Premorbid competence, role orientation, and gender differences in DSM-II versus DSM-III schizophrenic patients. - Glick, Marion; Quinlan, Donald M; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1987)
The study compared 71 patients diagnosed as schizophrenic or within the schizophrenia spectrum according to the second edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-II) with 66 patients who received similar diagnoses according to the third edition of the same manual (DSM-III). On measures of premorbid competence and role orientation, DSM-II and DSM-III schizophrenic patients obtained comparable scores. The DSM-III patients with schizophrenic versus schizophrenia spectrum diagnoses also obtained comparable scores on these measures. The gender differences in premorbid competence and role orientation that have consistently characterized DSM-II schizophrenics continued to characterize DSM-III schizophrenic and schizophrenia spectrum patients. The results suggest that findings previously obtained with DSM-II schizophrenics concerning premorbid competence and role orientation can be generalized to DSM-III schizophrenics. © 1987 American Psychological Association.
Keywords: adult; classification; competence; dept.psy; gender; human; major clinical study; orientation; schizophrenia